2017
DOI: 10.1136/flgastro-2016-100792
|View full text |Cite
|
Sign up to set email alerts
|

The impact of rifaximin-α on the hospital resource use associated with the management of patients with hepatic encephalopathy: a retrospective observational study (IMPRESS)

Abstract: ObjectiveTo compare all-cause and liver-related hospital resource use in the 6 and 12 months pre-rifaximin-α and post-rifaximin-α initiation in UK patients with hepatic encephalopathy (HE).DesignA UK multicentre, retrospective, observational study. Patients' medical records were reviewed for demographics, clinical outcomes and adverse events (AEs) to rifaximin-α. Details of hospital admissions/attendances in the 6 and 12 months pre-rifaximin-α and post-rifaximin-α initiation were extracted from hospital electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
44
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 18 publications
3
44
2
Order By: Relevance
“…There is now a robust evidence base to support rifaximin as a beneficial adjunctive therapy to lactulose in the prevention of recurrent episodes of overt HE, reducing the risk of hospitalisation and lowering inpatient length of stay and healthcare resource utilisation . Furthermore, it has been shown to improve health‐related quality of life in patients with cirrhosis and overt HE in remission and has been demonstrated to be safe and well tolerated in patients for long‐term maintenance of remission from overt HE .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is now a robust evidence base to support rifaximin as a beneficial adjunctive therapy to lactulose in the prevention of recurrent episodes of overt HE, reducing the risk of hospitalisation and lowering inpatient length of stay and healthcare resource utilisation . Furthermore, it has been shown to improve health‐related quality of life in patients with cirrhosis and overt HE in remission and has been demonstrated to be safe and well tolerated in patients for long‐term maintenance of remission from overt HE .…”
Section: Discussionmentioning
confidence: 99%
“…We did not observe a significant difference in hospital bed days, 8 in the rifaximin group vs 14 in the naïve group (mean effect estimate −6 [95% CI −12.23 to 0.76] days) and intensive care bed days, 1 in the rifaximin group vs 2 (mean effect estimate −1.40 [95% CI −3.76 to 0.97] days) in the naïve group. Moreover, recently published ‘real‐world' studies have shown that treatment with rifaximin was associated with a reduction in length of hospital stay and provides good value for money in terms of health economics and resource utilisation …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study by Hudson and colleagues, entitled the ‘IMPRESS’ study, represents further retrospective analysis of the impact of rifaximin on hospital resource use, this time from 13 sites around the UK 5. The purpose of the study was to provide ‘real-world’ data on the types and lengths of hospital admissions in patients who initiated rifaximin therapy for HE.…”
mentioning
confidence: 99%